1990
DOI: 10.1007/bf03258232
|View full text |Cite
|
Sign up to set email alerts
|

Piroxicam-β-Cyclodextrin in the Treatment of Headache

Abstract: SummaryPiroxicam-J3-cyclodextrin has been shown to give pain relief comparable to that with indomethacin and significantly greater than that with naproxen and piroxicam alone in the treatment of primary and migraine headaches. In addition, it would appear to be of use in the prophylaxis of migraine headaches, although further studies are required. The incidence of side effects with piroxicam-J3-cyclodextrin was substantially less than that with comparable drugs, particularly with regard to gastrointestinal sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Zolmitriptan (ZOTP) is one of the top three triptans that have the highest painrelief rates at two hours, whereas naratriptan is associated with fewer adverse effects [14]. In NSAIDs, piroxicam (PRCM), with increased absorption, has been shown to have a significantly greater analgesic effect than that of naproxen and was comparable with indomethacin [15]. In another similar study of the management of acute migraine pain, sublingual piroxicam showed significant pain relief and magnificent tolerability [16].…”
Section: Introductionmentioning
confidence: 99%
“…Zolmitriptan (ZOTP) is one of the top three triptans that have the highest painrelief rates at two hours, whereas naratriptan is associated with fewer adverse effects [14]. In NSAIDs, piroxicam (PRCM), with increased absorption, has been shown to have a significantly greater analgesic effect than that of naproxen and was comparable with indomethacin [15]. In another similar study of the management of acute migraine pain, sublingual piroxicam showed significant pain relief and magnificent tolerability [16].…”
Section: Introductionmentioning
confidence: 99%